Cubital Tunnel Syndrome - Modern Treatment Options - Sieradzka, Aleksandra; Krzysztof Szerej,; Alicja Kot,; Marta Wojtczak,; Natalia Myśliwiec,; Adrian Różycki,; Michał Pniak,; Paweł Miklis,; Maciej Mawlichanów,; Aleksandra Ciesielska, (Quality in Sport, 2025)
Introduction: Cubital Tunnel Syndrome (CuTS) is the second most prevalent compression neuropathy affecting the upper extremity. Patients typically present with symptoms of paresthesia in the fourth and fifth digits, accompanied by hand weakness and pain. Most patients respond well to conservative treatments, but some of them require surgical intervention. Aim of the study: The aim of this study is to assess and compare both surgical and conservative treatment methods. Conservative treatment for CuTS is typically pursued before surgical intervention, but there are no universally agreed-upon diagnostic and treatment algorithms for the condition. State of knowledge: Symptoms of Cubital Tunnel Syndrome manifest in approximately 5% of the general population. Etiological factors include repetitive pressure, stretching, flexion, or trauma to the elbow joint. If not appropriately managed, advanced stages of the disease may lead to irreversible muscle atrophy and hand contractures. Summary: Early diagnosis and intervention are the key factors in managing Cubital Tunnel Syndrome. The condition is frequently underdiagnosed, primarily due to patients' reluctance to seek treatment for their symptoms. No studies have definitively proven that one treatment approach is more effective than another. The choice of treatment should be based on the severity of the condition and the individual needs of the patient.